Eksperimen Pembelajaran Matematika Dengan Strategi Discovery Learning Dan Problem Based Learning Terhadap Hasil Belajar Ditinjau Dari Tingkat Kemandirian Belajar Pada Siswa Kelas VII SMP Batik Surakarta - Hardini Kurniani, Khoirida; , Prof. Dr. Sutama, M.Pd (2017)
This study aims to: (1) test the effect of a significant between discovery learning strategy and problem based learning strategy on mathematics learning outcome, (2) test the effect of a significant between of self-learning level on mathematics learning outcome, (3) test the effect of the interaction between the learning strategies and self-learning level on mathematics learning outcome. This study is a kind experiment. The population is around the seventh grade all students of SMP Batik Surakarta the academic year 2016/2017 with 302 students. Sample of this research is class VII H as the experiment class with 33 students and class VII I as the control class with 30 students. The sampling technique using cluster random sampling. Data collection techniques with methods of test, questionnaire, and documentation. Data were analyzed of variance of two difference cell. Research result with significance level α=5% was obtained (1) there is effect of a significant between discovey learning strategy and problem based learning strategy on mathematics learning outcome, (2) there is effect of a significant between self-learning on mathematics learning outcome, (3) there is not effect of the interaction between learning strategies and self-learning level on mathematics learning outcome. Keywords: discovery learning, problem based learning, self-learning, learning outcome